ANALISIS METODE RESITASI UNTUK MENUMBUHHKAN KARAKTER TANGGUNG JAWAB PESERTA DIDIK DI SDIU CAHAYA AL-FATIH KABUPATEN PANDEGLANG - Ahmad Fuadi Dakwan; Sholeh Hidayat; Ana Nurhasanah (Jurnal Pendidikan Dasar, 2023)
Abstract : The character of responsibility is an important character for a student to have because it is a basic character, a form of commitment and consistency in all behavior carried out. In the learning process at school, there are many ways that can be done to foster the character of responsibility, one of which is by using the recitation method in learning activities. The recitation method is considered to be able to foster the character of responsibility through the process of carrying out assignments. This research aims to describe the process of planning learning activities using the recitation method, to explain the process of implementing the recitation method and to analyze the implications of the recitation method process in cultivating students' responsible character in learning activities. The method used is a descriptive qualitative method with data collection techniques including interviews, observation and documentation. This research was conducted at SDIU Cahaya Al-Fatih, Pandeglang Regency as a place for collecting data, findings and results. The results of the research found that the implementation of learning using the recitation method at SDIU Cahaya Al-Fatih, Pandeglang Regency runs in accordance with the existing syntax starting from the assignment phase, assignment implementation phase and assignment responsibility phase, and has implications for the growth of students' responsible character as seen from Some indicators include students respecting time, not cheating, being active in learning activities and doing what is asked. Keywords: Learning, Recitation Method, Responsible Character.